Talent Management and Its Impact on Organizational Commitment: An Empirical Investigation of Indian Hospitality Industry. Issue 2 (June 2023) - Bahuguna, P.C.; Bangwal, Deepak; Kumar, Rajeev
The hospitality industry grapples with many workforces related issues like many other industries. Talent retention, turnover, commitment are significant issues in the hospitality industry in India. As a result of macro-level concerns such as the recent pandemic, the hospitality industry has started viewing talent management (TM) as a strategic lever to enhance organizational performance through committed and engaged employees. However, though organizational commitment has been an important research topic, only a few studies have been conducted on TM and organizational commitment in the Indian hospitality sector. Therefore, after the review of literature on the related field, the study tested three hypotheses to examine the causal relationship between TM practices and organizational commitment. Structural equation modelling using AMOS 26 was used to find empirical evidence in favour of the proposed hypotheses. The result of the study, showed that TM practices of the hospitality industry significantly influences the organizational commitment among the employees.